The polbeitics of federalization in Myanmar - Preecharush, Dulyapak (New York : Routledge, 2023)
"This book examines the trajectory of federalization in Myanmar's political development, evaluating the attitudes of different political actors towards, and negotiation strategies for, designing federalism. It argues that three factors drive federalization in Myanmar, namely constitutionalization, conflict management, and democratization. The confluence of these forces arrived at a critical juncture in 2011, the start of Myanmar's political transition, leading to significant changes in Myanmar's federation process. By analyzing the changes and continuities in federalism building, the book charts the dynamic pathway toward Myanmar's current federalization, revealing how periods of progress and stagnation reflect varying world views and the individual strategies of prominent political actors. Offering a systematic conceptual framework on federalism in Myanmar this will be a useful resource for student and scholars of Political Science, Comparative Politics and Southeast Asian Politics"--
Introduction -- Theories of Federalism and Federalization -- Historical Background of Myanmar's Federalization -- Causal Relationships in Myanmar's Federalization -- Negotiation Mechanisms in Myanmar's Federalization -- Current Political Development in Myanmar's Federalization -- Conclusion and Comparison.
Keywords: Federal government -- Burma; Burma -- History -- 1948-; Burma -- Politics and government -- 1948-; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Political Ideologies / General